2007
DOI: 10.1093/qjmed/hcm013
|View full text |Cite
|
Sign up to set email alerts
|

High levels of N-terminal pro B-type natriuretic peptide are associated with ST resolution failure after reperfusion for acute myocardial infarction

Abstract: Our data show a strong association between high levels of Nt-proBNP at admission and incomplete STR, suggesting that Nt-proBNP may be useful for early risk stratification in reperfusion therapy after acute myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
2
4
0
1
Order By: Relevance
“…[10][11][12][13][14] Sadanandan et al 15 reported that patients with BNP more than 80 pg/ml was associated with severity of coronary artery disease and multi -vessel disease as compare to patients with lower plasma BNP level. 16 L. Lorgis et al 16 This present study concluded that high BNP level is strongly associated with heart failure in patients presenting with STEMI.…”
Section: Discussionsupporting
confidence: 49%
“…[10][11][12][13][14] Sadanandan et al 15 reported that patients with BNP more than 80 pg/ml was associated with severity of coronary artery disease and multi -vessel disease as compare to patients with lower plasma BNP level. 16 L. Lorgis et al 16 This present study concluded that high BNP level is strongly associated with heart failure in patients presenting with STEMI.…”
Section: Discussionsupporting
confidence: 49%
“…17,22 Elevated serum NT-proBNP levels on admission in patients with STEMI have been known as a predictor of cardiovascular mortality. 33,34 The NT-proBNP is also a reliable independent predictor of sudden cardiac death after MI. 35 Modulation of NT-proBNP is multifactorial, depending on left ventricular dysfunction, remodeling, left intraventricular pressure, and residual myocardial ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…[7] не получили различий по ТИМ у больных РА с нормальным и повышенным уровнем NT-proBNP, что, вероятно, связано с низкой активностью РА. С другой стороны, имеются данные о взаимосвязи уровня NT-proBNP и распространенности коронарного атеросклероза при остром коронарном синдроме, а не только тяжести ХСН [29]. В некоторых исследованиях указывается на выделение NT-proBNP эндотелием сосудов, что может объяснить зависимость его концентрации от тяжести атеросклероза [30].…”
Section: зависимость чувствительности и специфичности уровня Nt-probnunclassified